Το μολυβδόβουλλο του Μιχαήλ Η΄ Παλαιολόγου «Τοῖς ἀθετοῦσι τὴν δίκην τοῦ σεκρέτου…» - ΓΚΟΥΤΖΙΟΥΚΩΣΤΑΣ Ανδρέας Ε. (Byzantina Symmeikta, 2012)
REMARKS ON THE SEAL OF MICHAEL VIII PALAIOLOGOS «Τοῖς ἀθετοῦσι τὴν δίκην τοῦ σεκρέτου…» After the recapture of Constantinople (1261) Michael VIII Palaiologos created a sekreton that functioned as permanent court of justice. Its institution is testified by a seal from the former collection of George Zacos, which now belongs to the Numismatic Museum of Athens. In this paper we republish this seal and make some remarks on the iconography and the metrical inscription of the obverse. In our view, it is the type of Theotokos Episkepsis (Virgo orans with the medallion of Christ on her bust) that is depicted on the obverse of the seal and not that of Blachernitissa as it has been maintained so far. It follows that the connection between the Blachernitissa type and justice administration, based on the testimony of this seal and other primary sources, can no longer be retained. Regarding the last word of the metrical inscription on the obverse it is also suggested that, except for “κάκης”, which has been recently suggested, “κἄλλη” can complement the inscription text.